Indigenous knowledge of key ecological processes confers resilience to a small‐scale kelp fishery. Issue 3 (5th May 2021) - Kobluk, Hannah M.; Gladstone, Keith; Reid, Mike; Brown, Kelly; Krumhansl, Kira A.; Salomon, Anne K.
Abstract: Feedbacks between social and ecological processes can lead to sustainable stewardship practices that support ecological resilience among harvested populations. This is evident along the world's coast lines, where Indigenous knowledge systems have facilitated millennia of human–nature coexistence. However, social–ecological conditions globally are quickly shifting, posing challenges for coastal Indigenous communities where customary harvest of ocean resources, such as kelps, needs to adapt to growing markets, novel climates and changing governance regimes. Consequently, a pressing need exists to determine how specific ecological and social variables drive key dynamics within coupled human–ocean systems. Motivated by the information needs of an Indigenous community on Canada's Pacific Coast, we co‐designed a traditional harvest experiment, field surveys and semi‐directed interviews with Indigenous resource users and managers to measure the ecological resilience of the feather boa kelp Egregia menziesii to harvest and determine what environmental variables most affected its recovery. We wove these results with information on current stewardship practices to inform future management of this slow‐growing perennial kelp based on Indigenous knowledge and western science. We found that Egregia recovered from traditional harvest levels faster than expected with minimal impact on its productivity because plants sprouted new fronds. In fact, traditional harvest levels of Egregia mimicked natural frond loss. Indigenous knowledge and empirical ecological evidence revealed the importance of individual plant size, site‐specific seawater temperature and wave exposure in driving Egregia recovery. Indigenous stewardship practices reflected these ecological relationships in the practice of selecting large plants from sites with healthy patches of Egregia . While we documented key social controls of harvest, current self‐reported harvest levels of kelp fronds were two times greater than the stated social norm, but only 1.2 times greater in terms of kelp biomass. Consequently, traditional harvest protocols facilitate Egregia recovery and promote its sustained use. However, its ecological resilience is susceptible to the erosion of customary practices and warming ocean temperatures. Co‐produced research that mobilizes multiple bodies of knowledge can enhance our understanding of social–ecological resilience, empower local decision makers and democratize the science and practice of natural resource management. ​ A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.